Visualization of PS/γ-Secretase Activity in Living Cells - Masato Maesako; Nicole M. Sekula; Anna Aristarkhova; Polina Feschenko; Lauren C. Anderson; Oksana Berezovska (iScience, 2020)
Summary: A change in Presenilin (PS)/γ-secretase activity is linked to essential biological events as well as to the progression of many diseases. However, not much is known about how PS/γ-secretase activity is spatiotemporally regulated in cells. One of the limitations is lack of tools to directly monitor dynamic behavior of the PS/γ-secretase in intact/live cells. Here we present successful development and validation of the Förster resonance energy transfer (FRET)-based biosensors that enable quantitative monitoring of endogenous PS/γ-secretase activity in live cells longitudinally on a cell-by-cell basis. Using these FRET biosensors, we uncovered that PS/γ-secretase activity is heterogeneously regulated among live neurons.